2015
DOI: 10.12968/jowc.2015.24.sup7.s4
|View full text |Cite
|
Sign up to set email alerts
|

Use of a copolymer dressing on superficial and partial-thickness burns in a paediatric population

Abstract: None declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…The results regarding time to reepithelialization in our study were comparable to those of a previous non-comparative study on the treatment of partial thickness burns in children with Suprathel ® [6, 9]. In two recent systematic reviews on the treatment of partial thickness burns in children, the mean time to reepithelialization in randomized controlled trials (RCT) that used other (semi)synthetic dressings varied between 7.5 and 23.6 days [1, 17].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results regarding time to reepithelialization in our study were comparable to those of a previous non-comparative study on the treatment of partial thickness burns in children with Suprathel ® [6, 9]. In two recent systematic reviews on the treatment of partial thickness burns in children, the mean time to reepithelialization in randomized controlled trials (RCT) that used other (semi)synthetic dressings varied between 7.5 and 23.6 days [1, 17].…”
Section: Discussionsupporting
confidence: 87%
“…Adherence of Suprathel ® was achieved when the Versajet ® system had been used, while no adherence was seen in most cases when superficial debridement had been performed. Three studies reported on the adherence of Suprathel ® to the wound bed in the treatment of partial thickness wounds and found excellent material adherence [6, 7, 9]. However, the effect of the extent of wound debridement on the adherence is not clear in these studies, because either different debridement techniques were used or no information was reported on the debridement technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A bőrhelyettesítő anyagok területén világszerte intenzív kutatás folyik, és korábbi összefoglalónk [14] [17,18]. Kiterjedt, mély égési sérülés kezelésénél az adóterület hiánya miatt rendkívüli kihívást jelent a bőrhiány pótlása.…”
Section: Bioszintetikus Bőrpótló Anyagokunclassified